Influence of jabbalabab.com Site Media as a German Online Learning Support on Learning Motivation of XI Grade Students at SMA Negeri 7 Malang - Azizah Rizki Nabilah; Deddy Kurniawan (Universitas Negeri Malang, 2022)
Knowing the influence of the uses of Jabbalab.com site media as a German online learning support on learning motivation of XI grade students of SMA Negeri 7 Malang is this researchs aim. T Quasi-experimental method used to identify the impact between each variables, which the result will answer whether Ha or H0 accepted or not. In this research, datas obtained from the results of pre-questionnaire and post-questionnaire. Finally, the result of this research is Ha was accepted, which sounds that there is an influence of the uses of Jabbalab.com site media as a German online learning support on learning motivation of XI grade students of SMA Negeri 7 Malang.